A Framework to Assess the Effectiveness of IMF Technical Assistance in National Accounts - Pastor Campos, Gonzalo (IMF Working Papers; Working Paper ;, 2009)
This paper analyzes the effectiveness of technical assistance provided by AFRITAC West (AFW) in the area of national accounts using the Fund's Technical Assistance Information Management System (TAIMS). The challenge has been to report on "ultimate outcomes" (i.e., the production and dissemination of national accounts statistics along best international practices) rather than on "inputs" (i.e., the number of national accounts missions fielded by AFW), as it has been the case to date. The paper concludes that the "ultimate outcome" of producing and disseminating robust national accounts is work in progress, with AFW's technical assistance efforts mainly focusing on source data assessments and methodological issues underpinning the compilation of national accounts. The pending challenge is to further support a more timely production and dissemination of national accounts data, as recommended in the Data ROSCs and by the IMF mission teams to AFW member countries.